In Vitro Characterization of Multilamellar Fibers with Uniaxially Oriented Electrospun Type I Collagen Scaffolds - Alireza Hooshmand-Ardakani; Tahereh Talaei-Khozani; Mehdi Sadat-Shojai; Soghra Bahmanpour; Nehleh Zarei-fard (Advances in Materials Science and Engineering)
Fabrication of an appropriate scaffold is critical in order to recapitulate the architecture and functionality of the native tissue. In this study, we attempted to create favorable collagen fiber alignment and multilamellar with uniaxially oriented layers, using a disc collector by turning mats 90 degrees horizontally at specific times. Different concentrations of rat tail-derived type I collagen (3, 6, 8% w/v) in 1,1,1,3,3,3-hexafluoroisopropanol (HFIP) are used for electrospinning affairs. The 6% w/v collagen at an applied voltage of 20 kV and collector rotation of 2500 rpm was selected to exhibit bead-free homogeneous nanofiber with fiber thickness of 0.14 ± 0.4 µm, maximum thickness of 0.5 ± 0.08 µm, and 60% porosity. Also, scanning electron microscope images of electrospun fibers showed 3D multilamellar scaffold with the goodness of 96.5% ± 0.8 in each aligned uniaxially oriented fiber layer. Cross-linking of collagen fibers with N-(3-dimethylaminopropyl)-N0-ethylcarbodiimide hydrochloride (EDC)/N-hydroxysuccinimide (NHS) reduced the fiber degradation rate and preserved the fiber morphology and alignment. The multilamellar mat showed significant increase in tensile strength and average breaking elongation in comparison with unilamellar mat. In vitro cell culture, using human adipose tissue-derived mesenchymal stem cells (hAT-MSCs) on cross-linked scaffold, showed improvement in cell proliferation, attachment, migration, and intercellular junction with a flattened morphology. Raman spectra revealed the preservation of collagen structure. In addition, Raman spectra of the cell containing scaffold were the same as those of an intact intervertebral disc as a sample to be used in engineering tissues. In conclusion, our results showed that the 3D multilamellar collagen nanofibrous scaffold is more appropriate for the tissues that have multilamellar structure.